Comparison of intra-cavity THG between the single- and multi-pass operations. (1st December 2017) - Xu, Shan; Gao, Shufang; Zhang, Ge
Highlights: It comparative studied intra-cavity THG between single- and multi-pass operations. The first THG plays a key role, which accounts for more than 70% of all power. The single-pass operation will be more useful in efficient THG laser. Abstract: Intra-cavity third harmonic generation was investigated comparatively in both single- and multi-pass operations from a side-pumped acousto-optic Q-switched Nd:YAG laser. Under the pump current of 19 A, 1.68 W and 2.2 W output power at 355 nm were obtained at 9.5 kHz in single and multi-pass THG operation respectively, with a power ratio of 76%. It clarified that the first THG process in multi-pass operation played a key role in the whole frequency-tripling process. The result provided the issue that efficient third harmonic laser could be achieved via optimizing the intra-cavity single-pass THG operation due to its high beam quality.